Repurposing Disulfiram (Tetraethylthiuram Disulfide) as a Potential Drug Candidate against Borrelia burgdorferi In Vitro and In Vivo - Hari-Hara S. K. Potula; Jahanbanoo Shahryari; Mohammed Inayathullah; Andrey Victorovich Malkovskiy; Kwang-Min Kim; Jayakumar Rajadas (MDPI AG, 2020)
Lyme disease caused by the Borrelia burgdorferi (Bb or B. burgdorferi) is the most common vector-borne, multi-systemic disease in the USA. Although most Lyme disease patients can be cured with a course of the first line of antibiotic treatment, some patients are intolerant to currently available antibiotics, necessitating the development of more effective therapeutics. We previously found several drugs, including disulfiram, that exhibited effective activity against B. burgdorferi. In the current study, we evaluated the potential of repurposing the FDA-approved drug, disulfiram for its borreliacidal activity. Our results indicate disulfiram has excellent borreliacidal activity against both the log and stationary phase B. burgdorferi sensu stricto B31 MI. Treatment of mice with disulfiram eliminated the B. burgdorferi sensu stricto B31 MI completely from the hearts and urinary bladder by day 28 post infection. Moreover, disulfiram-treated mice showed reduced expressions of inflammatory markers, and thus they were protected from histopathology and cardiac organ damage. Furthermore, disulfiram-treated mice showed significantly lower amounts of total antibody titers (IgM and IgG) at day 21 and total IgG2b at day 28 post infection. FACS analysis of lymph nodes revealed a decrease in the percentage of CD19+ B cells and an increase in total percentage of CD3+ T cells, CD3+ CD4+ T helpers, and naive and effector memory cells in disulfiram-treated mice. Together, our findings suggest that disulfiram has the potential to be repurposed as an effective antibiotic for treating Lyme disease.